Implementing sustainable development goals in the service sector - Nadda, Vipin 1970-; Tyagi, Pankaj Kumar 1979-; Vieira, Rubina Moniz; Tyagi, Priyanka (Advances in hospitality, tourism, and the services industry (AHTSI) book series, 2024)
This book will examine the various digital technologies such as the Internet of Things (IoT), Artificial Intelligence (AI), and Blockchain and their applications in the service sector to promote economic growth, create new job opportunities, and improve access to essential services such as education, healthcare, and financial services.